BIAS OF BEHAVIORAL FINANCE IN INVESTMENT DECISION: TRENDS AND FORECASTING - Lena Lestary; N Nugraha; I Waspada; M Sari; I Purnamasari (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Bias in financial behavior has always been an interesting discussion to study, because what the eye sees is what will be believed even if it is not necessarily the truth, also because everyone always has different points of view and thoughts when they get the same information. The many types of bias that are present in behavioral finance theory, of course, provide a lot of information that opens our eyes, that so many of our behaviors that we often don't realize in dealing with matters related to finance, it will have an impact on the situation as well as decision making related to finance, such as investment decisions. Differences in technology used, war, and even global conditions such as the Covid-19 pandemic that has hit the whole world, will certainly provide various inputs for the development of this science. The method used in this study is the Systematic Literature Review (SLR), where this study tries to map the trends that occur regarding bias in financial behavior, also tries to predict where research is going on this, so that later it is hoped that it will provide new input and views for the world of behavioral finance, what needs to be explored at this time, what contributions are needed today, and can be an attraction for other researchers to examine biases in behavioral finance theory.